Challenges, Strategies, and Perspectives for Reference-Independent Longitudinal Multi-Omic Microbiome Studies - Martínez Arbas, Susana; Busi, Susheel Bhanu; Queirós, Pedro; de Nies, Laura; Herold, Malte; May, Patrick; Wilmes, Paul; Muller, Emilie E. L.; Narayanasamy, Shaman (Frontiers in Genetics, 2021)
In recent years, multi-omic studies have enabled resolving community structure and interrogating community function of microbial communities. Simultaneous generation of metagenomic, metatranscriptomic, metaproteomic and (meta)metabolomic data is more feasible than ever before, thus enabling in-depth assessment of community structure, function and phenotype, thus resulting in a multitude of multi-omic microbiome datasets and the development of innovative methods to integrate and interrogate those multi-omic datasets. Specifically, the application of reference-independent approaches provides opportunities in identifying novel organisms and functions. At present, most of these large-scale multi-omic datasets stem from spatial sampling (e.g. water/soil microbiomes at several depths, microbiomes in/on different parts of the human anatomy) or case-control studies (e.g. cohorts of human microbiomes). We believe that longitudinal multi-omic microbiome datasets are the logical next step in microbiome studies due to their characteristic advantages in providing a better understanding of community dynamics, including: observation of trends, inference of causality and, ultimately, prediction of community behavior. Furthermore, the acquisition of complementary host-derived omics, environmental measurements and suitable metadata will further enhance the aforementioned advantages of longitudinal data, which will serve as the basis to resolve drivers of community structure and function to understand the biotic and abiotic factors governing communities and specific populations. Carefully setup future experiments hold great potential to further unveil ecological mechanisms to evolution, microbe-microbe interactions, or microbe-host interactions. In this article, we discuss the challenges, emerging strategies and best-practices applicable to longitudinal microbiome studies ranging from sampling, biomolecular extraction, systematic multi-omic measurements, reference-independent data integration, modelling and validation.